Medication adherence education for a patient with severe depression and psychotic symptoms: A case study - Zarma Zirani; Mamnuah Mamnuah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Medication nonadherence remains a problem among patients with mental disorders. According to 2023 data from the Ministry of Health, the rate of medication nonadherence reached 37.2%. Purpose: To describe changes in medication knowledge and adherence following a seven-day educational intervention in a patient with a mental disorder. Method: A qualitative descriptive approach using a case study design involving one patient diagnosed with nonadherence at Wisma Srikandi, Grhasia Mental Hospital in Yogyakarta. The nursing diagnosis was based on the Indonesian Nursing Diagnosis Standards (INDS). The intervention consisted of education on the benefits of medication, the “5 Rights of Medication” principles, and the consequences of non-adherence, delivered over 7 days for 15–25 minutes per day through lectures, discussions, and informational leaflets. Data were collected through observation, interviews, and pre- and post-tests. Results: After the intervention, patient adherence improved, as indicated by an increase in adherence scores from level 1 to level 5, as well as improved knowledge regarding the benefits of medication, the “5 Rights” of medication adherence, and the consequences of non-adherence. The signs and symptoms of the illness remained unchanged. Conclusion: Education is effective in improving knowledge and medication adherence among patients with mental disorders, thereby supporting the success of therapy and reducing the risk of relapse. Keywords: Adherence Level; Education; Medication.